Impact of Management Practices on Micro and Small Enterprise (MSEs) Performance in Marinduque, Philippines - Michael V. Capiña (Journal of Social Entrepreneurship Theory and Practice, 2021)
In the Philippines, micro and small enterprises (MSEs) comprise the largest part of the business economic undertakings and are among the most important development agents in rural communities like Marinduque. MSEs offer opportunities to poor people the possibility of earning income, training, work experience and employment. However, most of the micro and small enterprises in the country perform behind the neighboring ASEAN countries. Thus, assessing the impact of their management practices on operational functions (marketing, production, financial, human resources) and the significant relationship to MSEs performance (sales, production, and income) as the basis for government interventions. The study disclosed that management practices of 35 selected manufacturing MSEs on operational function is doing well with an overall mean of 3.70 interpreted as "Mostly Practiced". Of all the variables, marketing emerged to have the highest mean of 3.95, interpreted as "Mostly Practiced". What is alarming is the findings on human resources, which got the lowest mean of 3.40, interpreted as "Practiced". Overall performance in terms of sales, production, and income is 3.64, interpreted as "very satisfactory". Using Pearson, the operational business function has a positive correlation to performance. Based on the operational management practices, the following have a vital role for the success of MSEs such as type of business organization, decision-making process, creation of policy, rules, and regulations, planning and implementation, and management directions of the enterprise. As to these findings, programs of government will need to give emphasis on the weak areas and highlight the good practices as a basis for crafting tailored interventions for each MSEs.